The multiple-use of forests and the ecosystem services may generate higher returns than agricultural land rent in Ukrainian Polissya - Andrii Bilous; Roman Zadorozhniuk; Valentyn Bilous; Petro Diachuk; Oleksandr Labenko; Svitlana Bilous; Andrii Lashko; Yaroslav Kovbasa; Oleksandr Hrytsenko; Dmitry Schepaschenko; Fulvio Di Fulvio; Anatoly Shvidenko; et al. (European Journal of Forest Research, 2026)
Ecosystem service flows are acquiring paramount importance in designing land use policies, the setting local development priorities and social fabric in rural areas. Understanding the dynamics of the monetary value of forest ecosystem services (ES) is important for guiding private landowners in selecting appropriate management alternatives and motivating them to adopt multiple-use forest practices and expand forest cover, according to the New EU Forest Strategy for 2030. In this study, we estimated the spatio-temporal changes in biophysical parameters and the potential annual revenue from four major forest ES within a typical area of the Polissya region, Ukraine. The assessed ES included wood supply, CO 2 sequestration, mushroom and wild berry harvesting, and hunting. We further assessed the competitiveness of income generated under different combinations of ecosystem service utilization and forest regeneration types, comparing it to agricultural land rent using equivalent annual income valuation. We found that the total annual monetary flow from these ES increased by 19.3%, mostly due to forest land expansion and changes in forest structure of study area. On average, provisioning ES (both wood and non-wood forest products) contribute up to 90% of the total annual revenue, with similar contributions from each. This study underscores the competitive potential of forestry utilizing various ES as a viable land-use alternative for local landowners, with the highest expected discount rate of 2.3–3.5%. Our results highlight how forest-based management can serve as a key strategy for increasing forest cover while ensuring economic sustainability at the local level.